Retribalization dramaturgy of power in modern institution - Abuso, Julian Elloso
The initial purpose of this presentation is to examine a familiar institution, a school organization. in terms of the cultural-political process involved in institutional change. And by using retribalization as explanatory analytical device, that the line demarcating modern and so called tribal, simple societies in arbitrary, if not imaginary. The other purpose of this presentation is to contribute to the slowly evolving body of anthropology education literature in the Philippines.
Keywords: School management and organization -- Philippines; Faculty participation in administration -- Philippines; Educational leadership -- Philippines